Punicalagin Attenuates LPS-Induced Inflammation and ROS Production in Microglia by Inhibiting the MAPK/NF-κB Signaling Pathway and NLRP3 Inflammasome Activation - Lo J; Liu CC; Li YS; Lee PY; Liu PL; Wu PC; Lin TC; Chen CS; Chiu CC; Lai YH; Chang YC; Wu HE; et al. (Dove Medical Press, 2022)
Jung Lo,1,2 Ching-Chih Liu,3,4 Yueh-Shan Li,3 Po-Yen Lee,3,5 Po-Len Liu,6 Pei-Chang Wu,1,2 Tzu-Chieh Lin,7 Chi-Shuo Chen,8 Chien-Chih Chiu,9 Yu-Hung Lai,3,5,10 Yo-Chen Chang,3,5,10 Hsin-En Wu,3 Yuan-Ru Chen,3 Yu-Kai Huang,3,11 Shu-Pin Huang,1,12- 14 Shu-Chi Wang,15- 17 Chia-Yang Li3,16- 18 1Graduate Institute of Clinical Medicine, College of Medicine, Kaohsiung Medical University, Kaohsiung, 80708, Taiwan; 2Department of Ophthalmology, Kaohsiung Chang Gung Memorial Hospital and Chang Gung University College of Medicine, Kaohsiung, 83301, Taiwan; 3Graduate Institute of Medicine, College of Medicine, Kaohsiung Medical University, Kaohsiung, 80708, Taiwan; 4Department of Ophthalmology, Chi Mei Medical Center, Tainan, 71004, Taiwan; 5Department of Ophthalmology, Kaohsiung Medical University Hospital, Kaohsiung Medical University, Kaohsiung, 80708, Taiwan; 6Department of Respiratory Therapy, College of Medicine, Kaohsiung Medical University, Kaohsiung, 80708, Taiwan; 7Division of Cardiology, Department of Internal Medicine, Kaohsiung Medical University, Kaohsiung, 80708, Taiwan; 8Department of Biomedical Engineering and Environmental Sciences, National Tsing Hua University, Hsinchu, 30013, Taiwan; 9Department of Biotechnology, Kaohsiung Medical University, Kaohsiung, 80708, Taiwan; 10Department of Ophthalmology, School of Medicine, College of Medicine, Kaohsiung Medical University, Kaohsiung, 80708, Taiwan; 11Department of Neurosurgery, Kaohsiung Medical University Hospital, Kaohsiung, 80708, Taiwan; 12Department of Urology, Kaohsiung Medical University Hospital, Kaohsiung Medical University, Kaohsiung, 80708, Taiwan; 13Department of Urology, School of Medicine, College of Medicine, Kaohsiung Medical University, Kaohsiung, 80708, Taiwan; 14Ph.D. Program in Environmental and Occupational Medicine, College of Medicine, Kaohsiung Medical University, Kaohsiung, 80708, Taiwan; 15Department of Medical Laboratory Science and Biotechnology, Kaohsiung Medical University, Kaohsiung, 80708, Taiwan; 16Center for Cancer Research, Kaohsiung Medical University, Kaohsiung, 80708, Taiwan; 17Department of Medical Research, Kaohsiung Medical University Hospital, Kaohsiung, 80756, Taiwan; 18Department of Biological Science and Technology, National Pingtung University of Science and Technology, Pingtung, 91201, TaiwanCorrespondence: Shu-Chi Wang; Chia-Yang Li, Email shuchiwang@kmu.edu.tw; chiayangli@kmu.edu.twPurpose: Neurodegenerative diseases are associated with neuroinflammation along with activation of microglia and oxidative stress, but currently lack effective treatments. Punicalagin is a natural bio-sourced product that exhibits anti-inflammatory effects on several chronic diseases; however, the anti-inflammatory and anti-oxidative effects on microglia have not been well examined. This study aimed to investigate the effects of punicalagin on LPS-induced inflammatory responses, NLRP3 inflammasome activation, and the production of ROS using murine microglia BV2 cells.Methods: BV2 cells were pre-treated with punicalagin following LPS treatment to induce inflammation. The secretion of NO and PGE2 was analyzed by Griess reagent and ELISA respectively, while the expressions of iNOS, COX-2, STAT3, ERK, JNK, and p38 were analyzed using Western blotting, the production of IL-6 was measured by ELISA, and the activity of NF-κB was detected using promoter reporter assay. To examine whether punicalagin affects NLRP3 inflammasome activation, BV2 cells were stimulated with LPS and then treated with ATP or nigericin. The secretion of IL-1β was measured by ELISA. The expressions of NLRP3 inflammasome-related proteins and phospho IκBα/IκBα were analyzed using Western blotting. The production of intracellular and mitochondrial ROS was analyzed by flow cytometry.Results: Our results showed that punicalagin attenuated inflammation with reduction of pro-inflammatory mediators and cytokines including iNOS, COX-2, IL-1β, and reduction of IL-6 led to inhibition of STAT3 phosphorylation by LPS-induced BV2 cells. Punicalagin also suppressed the ERK, JNK, and p38 phosphorylation, attenuated NF-κB activity, inhibited the activation of the NLRP3 inflammasome, and reduced the production of intracellular and mitochondrial ROS by LPS-induced BV2 cells.Conclusion: Our results demonstrated that punicalagin attenuated LPS-induced inflammation through suppressing the expression of iNOS and COX-2, inhibited the activation of MAPK/NF-κB signaling pathway and NLRP3 inflammasome, and reduced the production of ROS in microglia, suggesting that punicalagin might have the potential in treating neurodegenerative diseases.Graphical Abstract: Keywords: punicalagin, microglia, NLRP3 inflammasome, MAPK, NF-κB